Integration of the Principle of Maqasid Al-Shariah in Managerial Decision making Process for Consumer Product of Shariah- Compliant Securities - Nurul Nadirah Binti Abu Hasan (Universiti Sains Islam Malaysia, 2024)
Despite the rapid expansions of Shariah-compliant products in the market, Shariah is still an unfamiliar subject for most practitioners and policymakers. Although there are numbers of Shariah-compliant securities in Malaysia, the current benchmark set by Shariah Advisory Council has given much attention to the aspect of the financial securities investment and not much interest on the aspect of management and operational practices. Besides, the disabilities among existing securities to sustain their status are needed to be addressed. It is crucial in order since their failure to acquaint may jeopardize consumers’ trust towards these securities in future especially among Muslims. Therefore, the present study aims to highlight the importance and relevancy to integrate Maqasid Al-Shariah in managerial decisionmaking process since it believed capably of improving the current managerial practices and sustaining existing Shariah-compliant securities'securities' status. Besides that, it also aims to analyze decision maker’s understanding in the industries regard to Maqasid Al- Shariah and to analyze their current practices in decision-making. It also aims to suggest suitable approaches to integrate the concept in the decision-making process. This study adopted a qualitative methodology. Using in-depth interview with the academia that had produced research regard to Maqasid Al-Shariah and decision making and decision-makers in the industries has been conducted to gain insight on theories, knowledge and practice. The data of this study was later analyzed using thematic analysis. Based on the findings, the importance to integrate Maqasid Al-Shariah in decision making is to preserve and protect Muslims community trust towards the securities and act as a religious obligation that falls under Muslim’s responsibilities. Besides that, it is also relevant to practice in the industry as an alternative for a better decision-making process and relevant to be practiced by non-Muslims as a norm. Decision-makers understanding in regard to Maqasid Al-Shariah and current practices in decision-making in the industries were also highlighted. Based on the interviews, suitable approaches to integrating Maqasid Al-Shariah were addressed which among the suggestions is to create awareness and understanding among practitioners and community regards to the concept. A new model of decisionmaking with the integrations of MaqasidAl-Shariah was also introduced.